Peran Ekstra Kurikuler Pramuka Dalam Pembentukan Karakter Disiplin Siswa - Muhamad Syafiudin; Agung Purwono (LP3M IAI Al Urwatul Wutsqo Jombang, 2022)
As time goes by, the value of discipline is fading. This makes teachers try to find solutions that can improve student discipline. With the implementation of the Scout Extra-Curricular, it is hoped that it can support the success of education in order to guide and foster the younger generation to create a complete human being. Because in character building, you can't just give theory, but you need a program that accompanies it. The formulation of the research problems include: How is the implementation of extra-curricular scouts and how the value of student discipline character can be formed through extra-scout activities in class V MI Miftahul ulum Cepokolimo? The research method used is descriptive qualitative, the researcher acts as a participant-observer during the scout extracurricular process. data were taken through observation, interviews, and documentation. The results showed that the extracurricular scouts were carried out twice a week with several activities such as routine training, hiking, and persami. The inculcation of disciplined character is proven by the achievement of students in keeping the learning schedule, facing temptations in procrastinating, self-discipline, and maintaining body condition.